Loosening chromatin and dysregulated transcription: a perspective on cryptic transcription during mammalian aging. (28th May 2021) - McCauley, Brenna S; Dang, Weiwei
Abstract: Cryptic transcription, the initiation of transcription from non-promoter regions within a gene body, is a type of transcriptional dysregulation that occurs throughout eukaryotes. In mammals, cryptic transcription is normally repressed at the level of chromatin, and this process is increased upon perturbation of complexes that increase intragenic histone H3 lysine 4 methylation or decrease intragenic H3 lysine 36 methylation, DNA methylation, or nucleosome occupancy. Significantly, similar changes to chromatin structure occur during aging, and, indeed, recent work indicates that cryptic transcription is elevated during aging in mammalian stem cells. Although increased cryptic transcription is known to promote aging in yeast, whether elevated cryptic transcription also contributes to mammalian aging is unclear. There is ample evidence that perturbations known to increase cryptic transcription are deleterious in embryonic and adult stem cells, and in some cases phenocopy certain aging phenotypes. Furthermore, an increase in cryptic transcription requires or impedes pathways that are known to have reduced function during aging, potentially exacerbating other aging phenotypes. Thus, we propose that increased cryptic transcription contributes to mammalian stem cell aging.